136k views
4 votes
6. Use the quadratic formula to solve the equation.-3x -x-3-0- 121.135-1t35B- 4135-It170

6. Use the quadratic formula to solve the equation.-3x -x-3-0- 121.135-1t35B- 4135-It-example-1

1 Answer

1 vote

we have

-3x^2-x-3=0

Using the quadratic formula

we have

a=-3

b=-1

c=-3

substitute in the formula


x=\frac{-(-1)\pm\sqrt[]{-1^2-4(-3)(-3)}}{2(-3)}
x=\frac{1\pm\sqrt[]{-35}}{-6}

Remember that

i^2=-1

so


x=\frac{1\pm i\sqrt[]{35}}{-6}=x=\frac{-1\pm i\sqrt[]{-35}}{6}

answer is option B

User Lorenzo Fiamingo
by
4.9k points